Handheld Ultrasound Diagnosis Of Extremity Fractures. Issue 2 (1st June 2004) - Brooks, A; Price, V; Simms, M; Ward, N; Hand, C
Abstract : Hand portable ultrasound has been validated in trauma patients using the FAST technique. The machine's light and rugged design make it suitable for military deployment and they have been successfully used on deployments in Kosovo, Afghanistan and Iraq. Ultrasound is widely accepted in the diagnosis of abdominal and thoracic trauma, however, little work exists on its use in extremity trauma. Although the diagnosis of fractures usually relies on X-ray this may not be readily available at Role 1 or 2. We successfully identified long bone fractures in three patients using hand portable ultrasound during Operation Telic. The technique and ultrasound findings are described and the current literature on this technique is reviewed.